Mapping the Intellectual Structure of Greenwashing and Purchase Intention Research: A Bibliometric Analysis of Scopus-Indexed Literature - Raras Puspita Wiji Utami; Tony Wijaya (Journal of Enterprise and Development (JED), 2026)
Purpose: This study aims to systematically map the development of literature on greenwashing and purchase intention by identifying publication trends, key contributors, geographic distribution, and the evolution of research themes.Method: Data were retrieved from the Scopus database, consisting of 83 English-language journal articles published between 2014 and 2026. The dataset was analyzed using bibliometric techniques with VOSviewer to examine publication patterns, influential contributors, geographic distribution, and thematic developments.Result: The findings show that publications on greenwashing and purchase intention increased substantially after 2020 and reached their peak in 2025. Research in this area is mainly concentrated in the Social Sciences and Business disciplines, with Sustainability (Switzerland) identified as the leading publication source. India and China emerged as the most productive countries, indicating the growing contribution of developing economies to this research field. The thematic analysis highlights green trust, green skepticism, consumer attitudes, and perceived risk as dominant themes in the literature.Practical Implications for Economic Growth and Development: The findings provide insights for companies to improve transparency in sustainability communication, for consumers to make more informed purchasing decisions, and for regulators to strengthen oversight of environmental claims. These efforts may enhance market transparency, promote sustainable consumption, and support long-term economic development.Originality/Value: This study offers a dedicated bibliometric mapping of greenwashing and purchase intention literature, providing a structured overview of its intellectual structure, thematic evolution, and future research directions.